Do side effects of antidepressants impact efficacy estimates based on the Hamilton Depression Rating Scale? A pooled patient-level analysis - Hieronymus, Fredrik (Transl Psychiatry, 2021)
The Hamilton Depression Rating Scale (HDRS-17) measures symptoms that may overlap with common antidepressant side effects (e.g., sexual dysfunction), thus making it possible that side effects of antidepressant treatment are erroneously rated as symptoms of depression, and vice versa. This study uses patient-level data from previously conducted antidepressant treatment trials to assess whether side effect ratings co-vary with HDRS-17 ratings. Data from all HDRS-17-rated, industry-sponsored pre- and post-marketing trials (n = 4647) comparing the serotonin and noradrenaline reuptake inhibitor, duloxetine, to placebo and/or to a selective serotonin reuptake inhibitor were pooled; three studies, which utilised sub-therapeutic doses, did not have symptom-level ratings available and could not be included. Severity was assessed for side effects related to sleep, somatic anxiety, gastrointestinal function, and sexual dysfunction. Analysis of covariance was used to assess the relation between these side effects and ratings of relevant HDRS-17-derived outcome parameters. Side effects related to sleep, somatic anxiety and sexual dysfunction significantly and exclusively associated with higher scores on HDRS-17 items measuring the corresponding domains. Side effects related to gastrointestinal function associated with higher HDRS-17 item scores on all assessed domains. Treatment outcome was significantly related to side effect severity when assessed using HDRS-17-sum (beta 0.32 (0.074), p < 0.001), but not when the HDRS-6-sum-score (beta 0.035 (0.043), p = 0.415) or the depressed mood item (beta 0.007 (0.012), p = .527) were used as effect parameters. That some HDRS-17 items co-vary with common antidepressant side effects suggests some of these adverse events are counted twice, potentially leading to an underestimation of antidepressant efficacy.